MAKNA DEMOKRASI DALAM KUMPULAN SAJAK TIRANI, BENTENG, DAN MALU (AKU) JADI ORANG INDONESIA KARYA TAUFIQ ISMAIL: ANALISIS DEKONSTRUKSI DERRIDA - , HASANUL RIZQA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Presently, there is a tendency for linking some literary works to a political situation. In the meantime, classification of generations in the history of Indonesian literature itself is wellacknowledged. Compared to any other generations emerged before or afterwards, Generation of â66 holds a unique position. Then, the political position of Generation of â66 can be described clearly by considering its poems, not its other literary texts. Among other poems created by poets of Generation of â66, poems written by Taufiq Ismail are the most representative ones. Therefore, the creation of poems by Taufiq Ismail can be related to the political chaos happened in 1966. That political chaos was caused by The Old Order acts in abuse of democracy, which led to its own collapse and the emerging of The New Order. However, years afterwards in 1998 Taufiq Ismail also found another chaos due to The New Orderâs corruption on democracy. Obviously, the creation of Taufiq Ismailâs poems can be related to the collapses of those regimes and the emerging regime of The New Order as well. This study is aimed for finding the meaning of democracy in the anthologies of poems Tirani, Benteng, and Malu (Aku) Jadi Orang Indonesia. The first two were created in 1966, whereas the last one was created in 1998. This study uses Derridaâs deconstruction as the method. Derridaâs deconstruction, however, claims that every logocentric text always contains oppositional structures. This study also uses Derridaâs ideas on democracy as the theoretical basis. Those ideas affirm that democracy has internal contradictions within itself. This study got results that the meaning of democracy in Tirani, Benteng, and Malu (Aku) Jadi Orang Indonesia was constructed as a closure. In the same way, that closure of democracy was built through the stabilization of vertical hierarchies, and of horizontal formations as well. Yet, deconstruction method showed that the logosâ on which all those hierarchies and formations existed were unstable, therefore the closure of democracy was finally broken. The deformity on the closure of democracy was also caused by the exclusion in the horizontal, democratic relationship, and by the stabilization of hierarchies in the vertical, democratic relationship. In conclusion, those anthologies of poems express a call to avoid any closure about the meaning of democracy. This call aims that all borderlines between the exclusive ones and the inclusive ones, or between the superior and the inferior, could always be diluted. Therefore, an effort could be soon made in order to end any destructive, political chaos. This study also found that those anthologies of poems calledâand have been callingâanyone to pay attention to the incalculable justice and mercy for all people in democracy. Key Words: the literature-politics relationship, Generation of â66, poems, democracy, deconstruction